Comparative study between the NLPI controller and the CPI controller - Mohammed Touhami; Pierre Sicard; Abdeljebar Hazzab; Fouad Mokhtari (Institute of Advanced Engineering and Science, 2019)
Unquestionably, the classic CPI controller dominates the industry and has the advantage of being simple and easy to implement. because its setting remains intuitive and more practical. On the other hand, these disadvantages lie in the fact that most of them reach a compromise in terms of speed of response and stability. Even worse, such an approach becomes insufficient at the increasingly demanding speeds demanded by the industry. in this context the NLPI controller is currently presented as an alternative. With its simple tuning method and robustness to process parameter variations, it stands out as a valuable addition to the toolbox of control engineering specialists. This paper aims to provide a simulation-based study using a MAS controlled by IFOC, comparing the PI controller system to the NLPI controller system. The results will be in favor of the last one.